Impact of Adapted Taekwondo Vs. Multicomponent Training on Health Status in Independent Older Women: A Randomized Controlled Trial - Herrera-Valenzuela, T (Frontiers Media SA, 2023)
This study, called the TKD and Aging Project, aimed to analyze and compare the effects of an adapted taekwondo program concerning multicomponent training on blood pressure, morphological variables, food consumption frequency, health-related quality of life (HRQoL), physical fitness, handgrip strength, and postural balance in independent older women. A randomized controlled trial study was conducted with parallel groups for 8 weeks (24 sessions of 60 min each), employing a double-blind design and incorporating repeated measures. Twenty-eight older women initially participated in the intervention. Three participants were excluded because they did not participate in the re-assessments. Thus, 14 older women from the adapted taekwondo group (TKD; age: 62.86 ± 2.38 years) and 11 from the multicomponent training group (MCT; age: 63.18 ± 1.94 years) participated in the final analysis. A two-factor mixed analysis of variance (ANOVA) model with repeated measures was performed to measure the time × group effect. The TKD showed significant improvements in the mental health (p = 0.024; ES = 0.91) and general health (p < 0.001; ES = 0.75) dimensions of the HRQoL, as well as in the chair stand (p = 0.001; ES = 1.18), arm curl (p < 0.001; ES = 2.10), 2-min step (p < 0.001; ES = 1.73), and chair sit-and-reach (p = 0.001; ES = 0.91) tests. Additionally, it showed a significant reduction in postural balance for the eyes-closed condition in the center of the pressure area (p = 0.021; ES = 0.89), mean velocity (p = 0.004; ES = 0.79), and mediolateral velocity (p < 0.001; ES = 1.26). However, the MCT showed significant increases in the general health (p = 0.013; ES = 0.95) dimension of the HRQoL and a significant reduction (p = 0.039; ES = 0.28) in the mediolateral velocity of postural balance for the eyes-closed condition. Multiple comparisons showed that the TKD scored significantly higher in the chair stand (p = 0.017; ES = 1.79), arm curl (p = 0.003; ES = 1.77), and 2-min step (p = 0.018; ES = 0.91) tests than the MCT. Compared to multicomponent training, taekwondo improves postural balance and provides better benefits in terms of physical fitness and HRQoL for older women. Therefore, it is possible to recommend it as a safe physical activity strategy, as long as it is well-dosed, since it showed high adherence to intervention in older women. Copyright © 2023 Valdés-Badilla, Guzmán-Muñoz, Herrera-Valenzuela, Branco, Hernandez-Martinez and Nobari.